Facile preparation of a novel biomass-derived H3PO4 and Mn(NO3)(2) activated carbon from citrus bergamia peels for high-performance supercapacitors - Gehrke, Veridiana (2021)
The increase in global energy demand, with consequent environmental effects caused by the extensive use of fossil fuels, resulted in the intensification of studies concerning the development of new sustainable processes of energy storage. Aiming to solve issues like complex fabrication processes, high cost and side effects on the environment, the use of activated carbons derived from residual biomass as electrodes for energy storage devices has attracted much attention. In this study, activated carbons derived from citrus bergamia peels activated with phosphoric acid (AC - H3PO4) and manganese nitrate (AC - Mn3O4) were produced, and its chemical, structural, morphological and electrochemical properties were evaluated as electrodes for supercapacitor. The electrochemical properties were studied by cyclic voltammetry, electrochemical impedance spectroscopy and galvanostatic charge/discharge, revealing the excellent performance of both AC - H3PO4 and AC - Mn3O4 , materials. The maximum value of specific capacitance was achieved by AC - Mn3O4, reaching 289 F.g(-1) at a current density of 0.1 Asg(-1). Outstanding results regarding energy density in ionic liquid electrolyte were also obtained, with values of 50.8 Wh kg(-1) at a power density of 240 W kg(-1).